Imaging internal structures in lithium-ion and sodium-ion batteries by neutron and x-ray tomography - Yerdauletov, M.; Napolskiy, F.; Daulbayev, Ch.; Nazarov, K.; Kenessarin, M.; Zhomartova, A.; Dakhiyev, Zh.; Bekbayev, А. (Recent Contributions to Physics, 2025)
This paper presents the application of combined non-destructive diagnostic methods—neutron and X-ray tomography, conducted using the TITAN neutron radiography and tomography facility at the WWR-K reactor, as well as the IMAX X-ray tomography facility, to visualize the internal structure of 2032 and 18650 battery cells provided by the Research, Design, and Technology Center for Electrochemical Engineering at Dubna State University. The obtained X-ray and neutron tomography data revealed inhomogeneities in the distribution of the base materials, as well as areas of low and high radiation attenuation, gaps, and voids at the boundaries between the electrodes and the battery case. The analysis results demonstrate the high efficiency of X-ray and neutron tomography for quality assessment during the manufacture of such batteries. The conducted test demonstration experiments allow for the development of methods for the combined application of these methods and provide a basis for their further use in the research and development of new battery systems.
Keywords: : x-ray tomography; neutron tomography; li-ion and sodium-ion battery